Integrating GeoGebra into the flipped learning approach to improve students' self-regulated learning during the covid-19 pandemic - Ishartono, Naufal; Nurcahyo, Adi; Waluyo, Mohamad; Prayitno, Harun Joko; Hanifah, Millenia (Journal on Mathematics Education, 2022)
The Covid-19 pandemic has forced an immediate transition from face-to-face learning in classrooms to online learning, including math learning. Mathematics with abstract working objects is not easy to learn online. So, an excellent self-regulated learning ability is required. So far, many efforts have been made to improve self-regulated learning in mathematics learning. However, there are still gaps in improving students' self-regulated learning ability in online mathematics learning, especially in relation to the integration of GeoGebra into the Flipped Learning approach. The purpose of this study is to examine the effectiveness of integrating GeoGebra into the Flipped Learning approach to improve students' self-regulated learning ability in learning mathematics online during the Covid-19 pandemic. This research is a quasi-experimental study with a pretest-posttest control group design to compare the effectiveness of a GeoGebra-integrated Flipped Learning approach. A conventional Flipped Learning approach and a conventional learning approach increase students' self-regulated learning level in constructing their understanding of mathematical concepts during online learning in the Covid-19 pandemic. The study involved 60 students randomly selected from one of Indonesia's private universities. They were divided into three groups representing each approach. Pretest and posttest results were quantitatively analyzed using Normalized Gain (N-Gain) Score, Cohen's d effect size, and statistical descriptive. The analysis results revealed that GeoGebra-integrated Flipped Learning is more effective in increasing students' self-regulated learning level in online mathematics learning than the other two approaches. It is expected that the results of this study can provide insights into alternative solutions for improving the quality of online mathematics learning by increasing the level of self-regulated learning of students.